Dynamics of Bilateral Trade and Labor Role in Case of Pakistan: A Gravity Estimation Model - Ali, Hina; Sattar, Munnaza; Iqbal, Sehrish; Nasir, Nazia (iRASD Journal of Economics, 2021)
The goal of this study paper is to look out for “Bilateral trade and labor migration in Pakistan a gravity estimation model. Trade among two states is known as bilateral trade. This paper analyzes the trade among Pakistan and 11 partners’ countries. Pakistan and 11 partners countries export and import goods for trade. Pakistan and partner countries sign different agreements for trade and the free trade agreement is one of the best agreements. For this research paper, we take the data from 2004-2019 in form of panel annual data for different countries taken from different sources these variables are used for this study Trade, gross domestics product distance, capital endowment , population scale , land endowment and relative importance of trade . Trade is a dependent variable GDP_dis, Cap_end, Pop_scal, Land_end, and RIMT are independent variables. Panel ARDL technique used for the estimation of results.